The Application of Mesenchymal Stem Cells in the Treatment of Liver Diseases: Mechanism, Efficacy, and Safety Issues - Yang, Ya; Zhao, Yalei; Zhang, Lingjian; Zhang, Fen; Li, Lanjuan (Frontiers in Medicine, 2021)
Mesenchymal stem cell (MSC) transplantation is a novel treatment for liver diseases due to the roles of MSCs in regeneration, fibrosis inhibition and immune regulation. However, the mechanisms are still not completely understood. Despite the significant efficacy of MSC therapy in animal models and preliminary clinical trials, issues remain. The efficacy and safety of MSC-based therapy in the treatment of liver diseases remains a challenging issue that requires more investigation. This article reviews recent studies on the mechanisms of MSCs in liver diseases and the associated challenges and suggests potential future applications.